Using Polya Steps To Solve Fraction Story Problems (Case Study In Class VII SMP) - Ronaldo Kho; Nike Irjayanti Praja; Pitriana Tandililing (Journal on Education, 2024)
This research is descriptive research using a qualitative approach. This research aims to describe the results of students' answers in solving mathematics story problems on fractional number operations based on Polya's steps in class VII SMP. Three research subjects were selected using a purposive sampling technique. Data collection was carried out using tests and non-tests (interviews). The test questions in this research are description questions, which consist of three questions. Based on the research results, it was found that (1) students were not able to understand the problem because students were unable to determine the information they knew and ask; (2) Students have not been able to make a solution plan because students have not been able to make a solution plan based on the information known and asked about the question; (3) Students have not been able to complete the completion plan because the students made a mistake in using the correct formula and were unable to complete the plan they had made; (4) students have not fulfilled the re-checking stage because students do not re-check the results they have obtained and are not sure about the answers.